Edukasi Keuangan bagi Warga Desa Lemoh Uner: Investasi sebagai Gaya Hidup: Financial Education for Rural Residents of Lemoh Uner: Investing as a Lifestyle - Vica Wilani Putri Kaparang; Stevie Alan Lasut; Samuel Benyamin Yohanis Saruan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The gap in financial literacy and inclusion is occurring not only in urban areas but also in rural areas. This gap indicates that people who use financial products or services are still not well-literate. Financial problems found in the field suggested that high living expenses make it difficult to set aside or save money, especially for investment purposes. Community service activities in Lemoh Uner Village focused on providing financial literacy through financial education for villagers. Community service activities were implemented through the preparation, implementation, reporting, and publication stages. The increase in financial literacy resulting from the implemented education was indicated by a change from a pre-test score of 38.89 percent to a post-test score of 76.85 percent, suggesting that financial education in Lemoh Uner Village increased local villagers' financial knowledge and literacy, especially regarding a conscious investment lifestyle. By increasing financial knowledge or literacy, it is also expected that Lemoh Village residents will have wiser financial attitudes. Community service through financial education can build awareness among Lemoh Uner Village residents about planning for future funds and investing intelligently and safely.